A comprehensive study of Ecuadorian adult patients with a mild and moderate presentation of COViD-19 - González-Andrade, Fabricio (2023)
Aim To characterize non-hospitalized patients with mild and moderate clinical presentation. Methods We performed an epidemiological, observational, descriptive, and cross-sectional study carried out in Ecuador, with 1,447 participants between 18 and 66 years, non-hospitalized, with a molecular RT-PCR test for SARS-CoV2. We analyzed demographic characteristics according to sex, age group, clinical findings, behavior after diagnosis, family and social behavior, sequelae, clinical evolution, type of exposure, and personal history. Results The sample analyzed had a mean age of 37 years (95% CI 18–66), women 713 individuals (49.27%), men 733 individuals (50.66%). Age group distribution was 18–30 years, 524 individuals (36.29%), 31–45, 538 individuals (37.26), and more of 45 years, 382 individuals (26.46%). 1416 individuals were mestizos (97.99%). According to the province of residence from Pichincha were 1019 patients (70.52%), followed by Imbabura, 93 patients (6.44%), and the others 335 (23.15%) patients come from all over the country. In women, the most common findings were fever >38C (54.40%), sputum (27.43%) and hypoxia (16.32%); HTN (5.75%) and hypercholesterolemia (3.69%). Men were more prevalent in all other findings. Comorbidities were more prevalent in all those over 45 years of age. COVID-19 antibodies test was positive in 416 patients (28.85%). Neuropsychiatric symptoms such as sleep disorders, generalized anxiety disorder, depressed mood, and chronic fatigue were more prevalent in men than women. Still, generalized anxiety disorder and chronic fatigue were more common in individuals of 31 to 45 years. 868 patients (60.07%) were in contact with a known infected person, 318 patients (22.02%) were health workers, and 782 patients (57.63%) were informed about work exposure. 545 patients (37.72%) were overweight, primarily women 310 (42.29%). 609 patients (42.65%) showed symptoms after the acute period, and 331 individuals (23.49%) reported some sequelae. Conclusion The epidemiological and clinical behavior of hospitalized and critical patients differs greatly from ambulatory or mild or moderate symptoms. It is essential to highlight those non-hospitalized patients constitute the predominant population of patients, hence the importance of adequate management that would directly affect the development of complicated forms and, consequently, the collapse of healthcare centers. It is vitally important to open more investigations that compare hospitalized and outpatient patients to have a clearer picture of the epidemic.